2021
DOI: 10.1097/cm9.0000000000001858
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis latency-associated antigen Rv1733c SLP improves the accuracy of differential diagnosis of active tuberculosis and latent tuberculosis infection

Abstract: Background:Differential diagnosis of active tuberculosis (ATB) and latent tuberculosis infection (LTBI) has been a challenge for clinicians in high TB burden countries. The purpose of this study was to improve the accuracy of differential diagnosis of ATB and LTBI by using fluorescent immunospot (FluoroSpot) assay to detect specific Th1 cell immune responses. The novel mycobacterium tuberculosis (MTB) latency-associated antigens Rv1733c and synthetic long peptides derived from Rv1733c (Rv1733c SLP) were used b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…All studies in table five have been assessed for sensitivity and specificity (if provided). Study four (22) uses FluoroSpot in testing both IFN-γ and IL-2 levels after stimulation from ESAT-6, CFP-10 separately and together or in combination with Rv1733c SLP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies in table five have been assessed for sensitivity and specificity (if provided). Study four (22) uses FluoroSpot in testing both IFN-γ and IL-2 levels after stimulation from ESAT-6, CFP-10 separately and together or in combination with Rv1733c SLP.…”
Section: Resultsmentioning
confidence: 99%
“…Study four (22) examined the use of FluoroSpot with Rv1733c, ESAT-6, and CFP-10. Sensitivity and specificity were found to be 84.2% and 83.3% respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Serra-Vidal et al (2014) on 60 latency-related Ags also showed that Rv1773 was the most immunogenic protein that can distinguish between non-infected, TBI, and ATB patients based on the IFN-γ response after 18 h of stimulation, with higher responses in TBI [ 206 ]. Another study on stimulation with synthetic long peptides derived from Rv1773c Ag (Rv1773c SLP), IL-2 secreting T-cells were significantly higher in TBI compared to ATB, but no significant results were obtained with IFN-γ secreting T-cells [ 208 ].…”
Section: Evaluation Of Mtb-derived Biomarkersmentioning
confidence: 99%